LAND USE CHANGES IN RURAL TOWN: A CASE STUDY OF KUALA NERANG, KEDAH - Othman, Abdul Ghapar; Jizan, Nurul Hanisah (PLANNING MALAYSIA, 2020)
Urbanization is the process of transforming a characteristically rural society into an urban one. The urban population is growing at an increasing rate while the rural population is declining, giving rise to imbalances in the development between urban and rural areas. The government’s strategy is to distribute the development to the major settlement centres in the rural areas, which are experiencing the same effects of urbanization as the urban areas in terms of changes to the use of land, especially the reduction of agricultural land and the increase in built-up areas. This study used the method of overlay in GIS applications to investigate land use changes, the speed of urban expansion and direction of development that has taken place from the period 2001 to 2018 in the town of Kuala Nerang, Kedah. This town has undergone a change in its status from a main settlement centre to a district administrative centre. Agricultural lands, which were targeted for development in the rural areas, have been converted into built-up areas. The speed of urban expansion has been slow, although some areas have recorded a higher rate. The development is moving towards the west along the main road connecting the major towns in this part of the state. The functions of the district administrative centre have influenced land use changes.